Interatomic coulombic decay in (HF)n,(n=2-3) clusters using CAP/EOM-CCSD method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2013)
The equation-of-motion coupled-cluster method along with the complex absorbing potential has been applied to study the interatomic Coulombic decay mechanism in hydrogen-bonded clusters. We have applied this method to calculate the lifetime of the F 2s inner-valence ionised state of (HF)(n) (n = 2-3) clusters. The lifetime is found to be very short and decreases substantially with increasing the number of HF monomer.
Keywords: complex absorbing potential (CAP); equation-of-motion coupled-cluster (EOM-CC); HF clusters; interatomic Coulombic decay (ICD)

Intermediate hamiltonian fock space multireference coupled cluster approach to core excitation spectra - Dutta, Achintya Kumar; Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
The Fock space multireference coupled cluster (FSMRCC) method provides an efficient approach for the direct calculation of excitation energies. In intermediate Hamiltonian (IH-FSMRCC) formulation, the method is free from intruder state problems and associated convergence difficulties, even with a large model space. In this paper, we demonstrate that the IH-FSMRCC method with suitably chosen model space can be used for the accurate description of core excitation spectra of molecules, and our results are in excellent agreement with the experimental values. We have investigated the effect of choice of model space on the computed results. Unlike the equation-of-motion (EOM)-based method, the IH-FSMRCC does not require any special technique for convergence and in singles and doubles approximation gives a performance comparable to that of the standard EOMEE-CCSD method, even better in some of the cases.

Implementation of the Z-vector method in the relativistic-coupled-cluster framework to calculate first-order energy derivatives: Application to the SrF molecule - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2015)
The molecular dipole moment and magnetic hyperfine-structure constant demand an accurate wave function far from the nucleus and in the near nuclear region, respectively. We, therefore, employ the so-called Z-vector method in the domain of relativistic-coupled-cluster theory to calculate the first-order property of molecular systems in their open-shell ground-state configuration. The implemented method is applied to calculate the molecular dipole moment and parallel component of the magnetic hyperfine-structure constant of the SrF molecule. The results of our calculation are compared with the experimental and other available theoretically calculated values. We are successful in achieving good accordance with the experimental results. The result of our calculation of the molecular dipole moment is in the accuracy of similar to 0.5%, which is clearly an improvement over the previous calculation based on the expectation value method in the four-component coupled-cluster framework [V. S. Prasannaa et al., Phys. Rev. A 90, 052507 (2014)]. Thus, it can be inferred that the Z-vector method can provide an accurate wave function in both the near and far nuclear region, which is evident from our calculated results.

Interatomic Coulombic decay in Neon-Helium cluster: a complex absorbing potential based equation-of-motion coupled cluster investigation - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2021)
The interatomic Coulombic decay (ICD) of the Ne(2s(-1)) and Ne(2s(-1)2p(-1)) states in neon-helium dimer is studied using highly accurate complex absorbing potential based equation-of-motion coupled cluster (CAP-EOMCC) method. The ICD decay process for the Ne(2s(-1)) state in neon-helium dimer is closed at its equilibrium bond distance. However, the decay channel is open at large bond distance of 6.2 angstrom. The decay channel for the double ionised Ne(2s(-1)2p(-1)) state is open at 3.46 angstrom. From our calculations, we have noticed that the decay rate of Ne(2s(-1)2p(-1)) state in neon-helium dimer is four times faster compared to the Ne(2s(-1)) state. We have also investigated how the decay rate of Ne(2s(-1)) state in neon-helium cluster varies in the presence of different helium environment. [GRAPHICS] .
Keywords: double ionised state; equation-of-motion coupled cluster (EOMCC); He droplet; interatomic Coulombic decay (ICD)

Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites